If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-28-6y=2(-6y+1)
We simplify the equation to the form, which is simple to understand
-28-6y=2(-6y+1)
Reorder the terms in parentheses
-28-6y=+(-12y+2)
Remove unnecessary parentheses
-28-6y=-12y+2
We move all terms containing y to the left and all other terms to the right.
-6y+12y=+2+28
We simplify left and right side of the equation.
+6y=+30
We divide both sides of the equation by 6 to get y.
y=5
| x^2/5=32 | | y+(y-50)=180 | | =4v*3v^4u^6*2u^7 | | -4x-13=6x+17 | | 3+c+6= | | 9+4x=3(x+4) | | 4-6m=(3m+14)-2(3m+5) | | 1.2t+3.4=-1.0 | | 6y+14=-7-y | | 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 |